Carbon dioxide and global temperatures: a causal and historical perspective - Crescenti, Umberto; Mariani, Luigi (Italian journal of engineering geology and environment, 2010)
<span data-sheets-value=""1":2,"2":"Climate variability in the last millennium has been investigated by scholars from all over the world. The paper discusses the studies and research that Umberto MONTERIN conducted on the Alpine area (northern Italy) in 1937 and focuses on the Medieval Warm Period (MWP - 950-1250) and the Little Ice Age (LIA - 1500-1850).These data add to the wider global knowledge base that many authors have built up over more than two centuries. This knowledge base not only challenges Mann’s “hockey stick” but, in our opinion, validates the thesis that climate change is mainly driven by natural determinants. This thesis is corroborated by the recent literature (see, for instance, EDDY, 1998; SHAVIV, 2003; SVENMARK, 2007; LOEHLE, 2007; ESPER & FRANK, 2009) and by the report edited by SINGER (2008).A realistic assessment of our planet’s past behaviour is imperative to acquire the capability of predicting the future climate. In other words, reliance should be made, without an ideologically preconceived vision, on data from multiple disciplines (geology, botany, agronomy, archaeology, forestry, social sciences, history, economics and so on). This idea is epitomised in this paper by the proposal to extend the geological principle of actualism to the future."" data-sheets-userformat=""2":13185,"3":"1":0,"10":1,"11":3,"12":0,"15":"Arial","16":8">Climate variability in the last millennium has been investigated by scholars from all over the world. The paper discusses the studies and research that Umberto MONTERIN conducted on the Alpine area (northern Italy) in 1937 and focuses on the Medieval Warm Period (MWP - 950-1250) and the Little Ice Age (LIA - 1500-1850).These data add to the wider global knowledge base that many authors have built up over more than two centuries. This knowledge base not only challenges Mann’s “hockey stick” but, in our opinion, validates the thesis that climate change is mainly driven by natural determinants. This thesis is corroborated by the recent literature (see, for instance, EDDY, 1998; SHAVIV, 2003; SVENMARK, 2007; LOEHLE, 2007; ESPER & FRANK, 2009) and by the report edited by SINGER (2008).A realistic assessment of our planet’s past behaviour is imperative to acquire the capability of predicting the future climate. In other words, reliance should be made, without an ideologically preconceived vision, on data from multiple disciplines (geology, botany, agronomy, archaeology, forestry, social sciences, history, economics and so on). This idea is epitomised in this paper by the proposal to extend the geological principle of actualism to the future.